Getting the Institutions Right for Gender Mainstreaming - Madsen, Diana Højlund (Kvinder, Køn & Forskning, 2011)
Getting the Institutions Right for Gender MainstreamningThe article focuses on processes of translating the global strategy of gender mainstreaming into practice at the local, Ghanaian level. Analysing mainstreaming from an institutional perspective, the roles of the national gender machinery and the gender desk officers in sector ministries are scrutinised according to critical elements for their functioning. The main finding suggests that successful mainstreaming processes to a large extent depend on individual women at the state level (femocrats) as a onsequence of a low level of institutionalisation of the strategy.